Descriptive Study of Advertising Message Strategy of Barista Special Blend by Top Coffee - Mohammad Ichsan Rasyid (International Journal of Entrepreneurship, Business, and Creative Economy, 2022)
Since 2017, For five consecutive years, Kopi Kapal Api has been the leading brand in Indonesia’s Top Brand chart in the instant roast and ground coffee category. The brand tagline, “Jelas Lebih Enak”, communicates the brand promise to deliver better taste, and has become one of the popular taglines among Indonesian consumers. Any coffee brand that wants to be perceived to be more excellent than Kopi Kapal Api needs to apply a distinguished Advertising Message Strategy to challenge the competition’s position. Therefore, this study aims to understand the distinguished applied Advertising Message Strategy by the newborn brand owned by an Indonesian Consumer Goods company, Barista Special Blend by Top Coffee. This study utilized The Elaboration Likelihood Theory Model as the analysis framework. This qualitative descriptive research collects data from literature studies and audiovisual advertising material from the official YouTube account of Top Coffee. The findings show that Barista Special Blend by Top Coffee endeavors to build a ‘Coffee Expert’ Brand Association and elaborate aesthetically on the process of serving a sophisticated Coffee-Making process made by the Barista Character. The study concludes that the Ad mainly uses the peripheral route to create expertise perception as the message strategy.